Pertumbuhan dan produksi Okra merah (Abelmoschus esculentus L. Moench) pada dosis pupuk kompos serasah yang berbeda dan pemangkasan - Rifna Nur Habiba; Widyati Slamet; Eny Fuskhah (Journal of Agro Complex, 2018)
The research aims was to investigate the interaction between dose of leaf compost and pruning on the growth and production of red okra. The research was assigned in basic design of completely randomized 4x2 factorial with three replications. The first factor was doses of leaf K (0, 50, 100, 150 kg N / ha). The second factor was pruning P (unpruned and pruned), each treatment was repeated three times. The parameters measured were stem diameter, number of leaves, number of fruits per plant, number of fruit per plot, and fruit weight per plot,. The data were analyzed statistically by of variance followed by Duncan's Multiple Range Test (DMRT). The results showed that there was no interaction effect at treatment doses of compost litter and pruning. Dosage of compost litter of 50 kg N / ha can increase the growth of girth, number of leaves, and the number of fruit per plot. Litter compost fertilizer dose of 100 kg N / ha can promote the growth and production of red okra. Pruning treatment can increase the production of red okra. Keywords : red okra, compost, leaf, pruning.